Silent brain infarcts and early cognitive outcomes after transcatheter aortic valve implantation: a systematic review and meta-analysis. (1st February 2021) - Woldendorp, Kei; Indja, Ben; Bannon, Paul G; Fanning, Jonathon P; Plunkett, Brian T; Grieve, Stuart M
Abstract: Background: Silent brain infarcts (SBIs) are frequently identified after transcatheter aortic valve implantation (TAVI), when patients are screened with diffusion-weighted magnetic resonance imaging (DW-MRI). Outside the cardiac literature, SBIs have been correlated with progressive cognitive dysfunction; however, their prognostic utility after TAVI remains uncertain. This study's main goals were to explore (i) the incidence of and potential risk factors for SBI after TAVI; and (ii) the effect of SBI on early post-procedural cognitive dysfunction (PCD). Methods and results: A systematic literature review was performed to identify all publications reporting SBI incidence, as detected by DW-MRI after TAVI. Silent brain infarct incidence, baseline characteristics, and the incidence of early PCD were evaluated via meta-analysis and meta-regression models. We identified 39 relevant studies encapsulating 2408 patients. Out of 2171 patients who underwent post-procedural DW-MRI, 1601 were found to have at least one new SBI (pooled effect size 0.76, 95% CI: 0.72–0.81). The incidence of reported stroke with focal neurological deficits was 3%. Meta-regression noted that diabetes, chronic renal disease, 3-Tesla MRI, and pre-dilation were associated with increased SBI risk. The prevalence of early PCD increased during follow-up, from 16% at 10.0 ± 6.3 days to 26% at 6.1 ± 1.7 months and meta-regression suggested an association between the mean number of new SBI and incidence of PCD. The use of cerebral embolic protection devices (CEPDs) appeared to decrease the volume of SBI, but not their overall incidence. Conclusions: Silent brain infarcts are common after TAVI; and diabetes, kidney disease, and pre-dilation increase overall SBI risk. While higher numbers of new SBIs appear to adversely affect early neurocognitive outcomes, long-term follow-up studies remain necessary as TAVI expands to low-risk patient populations. The use of CEPD did not result in a significant decrease in the occurrence of SBI. Graphical Abstract: